Influence of the specific surface of the nanostructured TiO2 membrane on efficiency of the photovoltaic cell - Serikov, T.M.; Ibrayev, N.Kh.; Amanzholova, G.S. (Publishing House of the KarSU named after E.A.Buketov, 2016)
Membranes of nanorods of titanium dioxide are synthesized in the work by hydrothermal method. On a surface of nanorods nanoparticles of titanium dioxide have been settled. By the nitrogen adsorption method (BET method) sizes of specific surface have been measured, full pore volume, distribution of pore by the sizes in the membranes formed by nanorods (NRs) and nanorods with the spherical nanoparticles of titanium dioxide (NRs+NPs) settled on a surface. By the method of scanning electronic microscopy morphology of a surface of the synthesized membranes has been studied. On a basis of the synthesized membranes solar cells have been collected by sensibilized dye. Volt-ampere characteristics and efficiency of cells are measured.
Keywords: titanium dioxide nanorods; solar cell efficiency; specific surface area